1987
DOI: 10.1159/000298855
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Excretion of 6β-Hydroxycortisol and Estriol at 32 Weeks Gestation

Abstract: We have previously shown a marked diurnal variation in the excretion of cortisol and 6Β-hydroxycortisol at 36–38 weeks pregnancy with no variation in estrogen excretion. Since others have shown a reciprocal relationship between plasma levels of estriol and cortisol at 30–35 weeks of pregnancy, we decided to determine whether a similar relationship was present in urinary concentrations of cortisol, 6Β-hydroxycortisol and estriol at this gestational age. A significant variation in excretion of both cortisol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…We also observed the same diurnal pattern that is present in non‐pregnant women, higher morning cortisol and lower evening cortisol 73,79 . The few small studies that have measured both AM and PM cortisol in pregnant women have reported similar results 58,62–64 …”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…We also observed the same diurnal pattern that is present in non‐pregnant women, higher morning cortisol and lower evening cortisol 73,79 . The few small studies that have measured both AM and PM cortisol in pregnant women have reported similar results 58,62–64 …”
Section: Discussionsupporting
confidence: 80%
“…Most studies of cortisol in pregnant women have collected samples in a clinic or laboratory, settings that may be stressful for some but not all women. Studies in pregnant women with saliva samples collected at home have been modest in size ( n = 7–121) 5,54 , 58 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations